Augmentation of Gut Microbiome improves Melatonin concentration, Sperm parameters and testicular Steroidogenesis in light-polluted Rat. (African Journal of Biomedical Research, 2022)
Altering the natural circadian rhythm by prolonged exposure to light is known to alter reproductive functions in many species including humans. However, it is not clear if augmentation of the gut microbiome can protect male reproductive function when exposed to light pollution. The current study was designed to investigate if the administration of probiotics (pro) will mitigate the disruptive effect of light pollution on melatonin concentration, semen parameters and testicular steroidogenesis in the rat. Thirty male Sprague-Dawley rats were randomized into six groups (n=5) consisting of the no-Pro/12hrs group that had 12:12 hrs light:dark cycle only; the Pro/12hrs group that had 12:12 hrs light:dark cycle plus probiotic supplementation; the no-Pro/16hrs that had 16:8 hrs light:dark cycle; the Pro/16hrs that had 12:12 hr light:dark cycle in addition to probiotic supplementation; the no-Pro/24hrs that had 24:0 hrs light:dark cycle; and the Pro/24hrs that had 24:0 hrs light:dark cycle plus probiotic supplementation.  Each animal in the probiotic groups was fed a 10×106 colony-forming unit of lactobacillus acidophilus and Bifidobacterium bifidum every other day. Experiment lasted for 21 consecutive days. Probiotic administration significantly (p